2022
DOI: 10.7189/jogh.12.04030
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia in neonatal hypoxic encephalopathy: A systematic review and meta-analysis

Abstract: Background Therapeutic hypothermia (TH) is regarded as the most efficacious therapy for neonatal hypoxic encephalopathy. However, limitations in previous systematic reviews and the publication of new data necessitate updating the evidence. We conducted this up-to-date systematic review to evaluate the effects of TH in neonatal encephalopathy on clinical outcomes. Methods In this systematic review and meta-analysis, we searched Medline, Cochrane Library, Embase, LIVIVO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 105 publications
1
28
0
2
Order By: Relevance
“…Although the initiation of the LyTONEPAL cohort preceded the main publications on the impact of TH on mild HIE [21], our study identi ed an overall rate of 36.5%, 32.6%, 44.3% and 17.6% of neonates with a rst pH ≥ 7.0, rst lactate levels < 11.0 mMol/L, Apgar score ≥ 5 at 5 min, and resuscitation at birth with at least mask ventilation, respectively. This nding is in line with the actual concerns of the temporal change of recorded severity of HIE in cooled babies [20,22].…”
Section: Discussionmentioning
confidence: 76%
“…Although the initiation of the LyTONEPAL cohort preceded the main publications on the impact of TH on mild HIE [21], our study identi ed an overall rate of 36.5%, 32.6%, 44.3% and 17.6% of neonates with a rst pH ≥ 7.0, rst lactate levels < 11.0 mMol/L, Apgar score ≥ 5 at 5 min, and resuscitation at birth with at least mask ventilation, respectively. This nding is in line with the actual concerns of the temporal change of recorded severity of HIE in cooled babies [20,22].…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, practices and opinions vary widely regarding infants with severe CHD. Although only few cases of neonates with severe CHD treated with TH have been published, and infants with (major) congenital anomalies have been excluded in many randomized trials on TH, even neonates with severe CHD are offered TH in a variety of clinical scenarios in some centers ( 9 , 12 , 23 ). Almost one-third of departments offer TH after perinatal asphyxia in neonates with severe CHD, but when asked for their personal opinion, only 20.3% of the respondents opposed TH.…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 survey of cooling centers in the United Kingdam found that a large number of centers offer TH to neonates with only mild HIE ( 28 ). It appears that TH is increasingly being used in neonates with indications other than those on which randomized trials of TH are based ( 2 , 9 ). This may be due to the fact that TH is the only therapeutic intervention for NE with beneficial neurologic outcomes to date, although this effect has been proven only in neonates with NE secondary to an intrapartum asphyxia event ( 2 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matthew et al concluded that effects of TH on mortality are uncertain but that one cannot deny the protective effect on neurodevelopmental outcomes seen in survivors and recommend that further studies be conducted in diverse settings. (17) There are limited studies reporting on effect of TH in sub-Saharan Africa. A small randomized clinical trial from Uganda reported a high mortality in neonates managed with TH compared to those receiving standard care (33% vs 6.7%) (18).…”
Section: Introductionmentioning
confidence: 99%